The Transformative Power of Virtual Hospitals for Revolutionising Healthcare Delivery - Alexandre Vallée; Maxence Arutkin; Maxence Arutkin (Frontiers Media S.A., 2024)
Objectives: The objective of this narrative review is to explore the advantages and limitations of VHs in delivering healthcare, including access to specialized professionals, streamlined communication, efficient scheduling, integration of electronic health records, ongoing monitoring, and support, transcending geographical boundaries, and resource optimization.Methods: Review of literature.Results: The national healthcare systems are facing an alarming rise in pressure due to global shifts. Virtual hospitals (VH) offer a practical solution to numerous systemic challenges, including rising costs and increased workloads for healthcare providers. VH also facilitate the delivery of personalized services and enable the monitoring of patients beyond the conventional confines of healthcare settings, reducing the reliance on waiting medicine carried out in doctors' offices or hospitals.Conclusion: VH can mirror the conventional healthcare referral system.